KEMAMPUAN LITERASI BACA TULIS DALAM PEMBELAJARAN MUATAN LOKAL MURID KELAS IV SD NEGERI NO.73 BONTORITA 1 KABUPATEN TAKALAR : Reading And Writing Literacy Skills in Local Content Learning for Fourth Grade Students at State Elementary School No. 73 Bontorita 1 Takalar Regency - Putri, Novy Zaskia; Amir, Djohar; Rahim, Abdul (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the Literacy Ability of Reading and Writing in Local Content Learning of Class IV Students of SD Negeri No.73 Bontorita 1 Takalar Regency. This research is a quantitative descriptive research design. The population of this study were fourth grade students of SD Negeri No.73 Bontorita 1 Takalar Regency. The sample withdrawal used in this study was the Total Sampling technique. Based on the assessment criteria, the overall level of students' reading literacy skills is at an incapable level. This can be seen from the assessment results that it turns out that students who get the minimum completeness criteria (KKM) score are 1 person with a percentage of 3% and those who get scores below the KKM are 29 students with a percentage of 97% and based on the assessment criteria the overall level of students' writing literacy skills is at an incapable level. This can be seen in the ability of writing literacy, the assessment results showed that there were 6 students with a percentage of 20% and 24 students with a percentage of 80% who scored below the minimum completeness criteria (KKM).